2019
DOI: 10.1007/s00417-018-04222-w
|View full text |Cite
|
Sign up to set email alerts
|

Fundus autofluorescence and spectral domain optical coherence tomography as predictors for long-term functional outcome in rhegmatogenous retinal detachment

Abstract: Fundus autofluorescence and spectral domain optical coherence tomography as predictors for long-term functional outcome in rhegmatogenous retinal detachment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…e metabolic stress induced on the retina by the detachment and the following surgical intervention can be observed by mapping fundus fluorophores [7]. ese naturally autofluorescent substances can be imaged with fundus autofluorescence (AF), a noninvasive modality that provides an indirect marker of the metabolic activity of the outer retina and the balance between photoreceptor outer segment turnover and RPE phagocytotic ability [8].…”
Section: Introductionmentioning
confidence: 99%
“…e metabolic stress induced on the retina by the detachment and the following surgical intervention can be observed by mapping fundus fluorophores [7]. ese naturally autofluorescent substances can be imaged with fundus autofluorescence (AF), a noninvasive modality that provides an indirect marker of the metabolic activity of the outer retina and the balance between photoreceptor outer segment turnover and RPE phagocytotic ability [8].…”
Section: Introductionmentioning
confidence: 99%
“…13 Optical coherence tomography (OCT) has been previously used to evaluate macular alterations occurring after surgery for RRD repair, helping additionally in defining prognostic factors that may predict the postoperative anatomic and visual outcome. 412 Coppola et al reported that the main structural cross-sectional OCT findings after vitreoretinal surgery for RRD included subretinal fluid, subretinal blebs, retinal folds, subretinal perfluorocarbon liquids, macular alterations related to silicone oil, epiretinal membranes, proliferative vitreoretinopathy, cystoid macular edema, macular holes, and recurrent retinal detachment. 13 Additionally, thinning of macular ganglion cell-inner plexiform layer has been observed in patients with RRD treated with PPV, 14 while thickening of peripapillary retinal nerve fiber layer in successfully operated RRD eyes using vitrectomy and silicone oil endotamponade has been also reported.…”
Section: Introductionmentioning
confidence: 99%
“…However, the anatomical success is not always linked to functional visual recovery and involvement of the macula in the retinal detachment pathogenesis is one of the most important prognostic factors for visual prognosis [ 8 ]. In clinical practice the combination of optical coherence tomography (OCT) and optical coherence tomography angiography (OCTA) has allowed a more detailed study of some suboptimal functional recovery causes after surgery, including a refractory cystoid macular edema (CME), persistent subretinal fluid (SRF) and epiretinal membrane (ERM) combined with alteration of the inner segment/outer segment (IS/OS) [ 9 , 10 , 11 , 12 , 13 ], and a more accurate analysis of the pathophysiological changes occurring in the macular microcirculation in retinal diseases, such as diabetic retinopathy, age-related macular degeneration, retinal vein occlusions, uveitis and macular telangiectasias [ 14 ]. Several studies have investigated retinal microvasculature and its changes in ocular diseases after vitreoretinal surgery.…”
Section: Introductionmentioning
confidence: 99%